2014
DOI: 10.4103/2348-2915.133942
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 in oral submucous fibrosis: An immunohistochemical study - Understanding the pathogenesis

Abstract: Background:The development of fibrosis is pathognomic in the potentially malignant oral disorder, oral submucous fibrosis (OSF). Strong evidence exists to implicate the chewing of areca nut in the pathogenesis of the lesion. The constituents of areca nut activate several pro-fibrotic cytokines, chiefly transforming growth factor beta 1 (TGF-β1), which leads to an increased deposition and decreased degradation of extracellular matrix and collagen. TGF-β1 probably represents the major pathway in the deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This suggested that the fibrotic change in OSMF may be a reparative process in response to the injury by the noxious agents in areca nut, and thus, targeting this molecule may help in controlling the progression of the disease. [ 13 ] Pant et al . showed in their study that Maria et al .…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the fibrotic change in OSMF may be a reparative process in response to the injury by the noxious agents in areca nut, and thus, targeting this molecule may help in controlling the progression of the disease. [ 13 ] Pant et al . showed in their study that Maria et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was concluded that the pathogenesis of OSF is linked to TGF-β1 pathway which is the main initiator of collagen production. 1,7 Transforming growth factor beta signaling pathway is initiated by attachment of ligand to transmembranous serine/threonine kinase Type I and II receptors, which in turn activates the cascade of SMAD signal transduction pathway. 31,32 In addition, a number of collagen gene promoters which were induced by TGF-β1and dependent upon SMAD-3 have been demonstrated in human dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…5 This led to rigidity of the oral mucosa causing limitation of opening the mouth and difficulty in eating or maintaining oral health. 6 The pathogenesis of the disease is still not confirmed yet and the disease is thought to be a multifactorial condition 7 ; where chewing of betel quid/areca nut has been found as one of the most significant risk factors for OSF. 8 It has been found that Arecoline (alkaloid component of the betel quid) played an important role in the pathogenesis of OSF as it increased the synthesis of collagen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to epidemiological data, chewing betel nuts is also most significant risk factors for OSMF. 19 In China, 62.3% of OSMF patients consume betel nuts. Smoking, tobacco chewing, and alcohol consumption, all have been linked to an increased risk of OSMF.…”
Section: Introductionmentioning
confidence: 99%